Fixed‐Life or Rechargeable Battery for Deep Brain Stimulation: Which Do Patients Prefer?. Issue 4 (22nd August 2018) - Khaleeq, Tahir; Hasegawa, Harutomo; Samuel, Michael; Ashkan, Keyoumars
Abstract : Background: Deep brain stimulation (DBS) is increasingly used to treat a wide variety of neurological and psychiatric disorders. Implantable pulse generators (implantable pulse generators/batteries) for DBS were originally only available as a nonrechargeable option. However, there is now a choice between fixed‐life and rechargeable batteries, with each having their own advantages and disadvantages. The extent of patient involvement in the choice of battery and the factors that matter to them have not been well studied. Methods: Thirty consecutive adult patients with movement disorders attending a pre‐DBS clinic were offered a choice of fixed‐life or rechargeable battery and completed a questionnaire after the consultation on which factors influenced their decision. Results: Nineteen patients (63%) chose the fixed‐life battery and 11 patients (37%) chose the rechargeable battery. There were no significant differences in age, sex, underlying disease, disease duration or Unified Parkinson's Disease Rating Scale (UPDRS) (part 3) score (for patients with Parkinson disease) between those who chose the fixed‐life vs. rechargeable battery. Most patients were not concerned about the size of the battery. Equal numbers were concerned about surgery to replace the battery, and less than half were concerned about the need to recharge the battery. More than half of patients felt that an acceptable charging frequency was monthly or yearly, and all patients felt that an acceptable charging duration was less than 1 hour, with half of all patients choosing less than 30 min. The main reasons cited for choosing the fixed‐life battery were convenience and concern about forgetting to recharge the battery. The main reason for choosing the rechargeable battery was the avoidance of further surgery. Discussion: Most patients in this adult cohort with movement disorders chose the fixed‐life battery. The better lifestyle associated with a fixed‐life battery is a major factor influencing their choice. Rechargeable batteries may be more acceptable if the recharging process is improved, more convenient, and discreet. Conflict of Interest: The authors' institution has received educational grants from Medtronic, Abbott, and Boston Scientific companies.